New fermions and a vectorlike third generation in SU(3)(C)circle times SU(3)(L)circle times U(1)(N) models - Pleitez, Vicente [UNESP] (American Physical Soc, 1996)
We study two 3-3-1 models with (i) five (four) charge 2/3 (-1/3) quarks and (ii) four (five) charge 2/3 (-1/3) quarks and a vectorlike third generation. Possibilities beyond these models are also briefly considered.